ANALISIS BIBLIOMETRIK: PERKEMBANGAN PENELITIAN ETNOMATEMATIKA DI SEKOLAH DASAR (2008-2023) - Nisaul Hikmiah, Alien; Mariana, Neni; Wiryanto, Wiryanto (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
The importance of bridging mathematics learning with everyday life around students is called ethnomathematics. The aim of this research is to look at ethnomathematics research trends, examine how to classify ethnomathematics, and review opportunities for ethnomathematics topics in elementary schools to become future research trends. This research data uses the Scopus database with VOSviewer. Data obtained by Scopus with the keywords "ethnomathematic" and "elementary school" with 15 years and  a time limit of 2008 to 2023 contained 29 publications and 126 citations, with the most citations in 2012. This research shows that the number of scientific articles for publications on ethnomathematics in elementary schools fluctuates. The network cluster shows several keywords that often appear with 3 network clusters, namely the largest are the words ethnomathematics with ecocultural mathematics and elementary school. The latest theme trends include four themes is ethnomathematics pada building space, mathematics, and bengkalis malay community. There is a very clear publication with the keyword ethnomathematics.